The health gap and HRQoL inequalities in Greece before and during the economic crisis - Yfantopoulos, John; Chantzaras, Athanasios; Yfantopoulos, Platon (Frontiers in Public Health, 2023)
Objective The aim of this study was twofold: (i) to assess the health gap among young socio-economic groups generated by the economic crisis in Greece and (ii) to investigate HRQoL (Health Related Quality of Life) inequalities using the Theil index. Methods The EQ-5D-5L instrument was administered to a sample of 4,177 young individuals in Greece, mean age 22.3 (±SD 4.8) and 53.8% males, and 46.2% females. The Greek version of the EQ-5D-5L instrument was used in a web-based questionnaire to collect data. Subjects were asked to assess their subjective health status during the economic crisis of 2016 using the EQ-5D-5L instrument, and to recall their health before the crisis of 2009. The health gap was assessed on a Visual Analogue Scale (EQ-VAS), the EQ-5D-5L Index, and the five dimensions of the EQ-5D-5L instrument. Regression analysis was employed to measure the effects of the economic crisis on age, sex, education, and income on the EQ-VAS and EQ-5D-5L. Theil index was used to assess HRQoL inequalities. Results The economic crisis brought a significant deterioration in the HRQoL of young Greeks. The EQ-VAS was reduced during the crisis by −10.05% (p < 0.001) and the EQ-5D-5L index declined by −19.61% (p < 0.001). The prevalence of the health gap in each dimension of the EQ-5D-5L was also significant in terms of deterioration of Mobility [change by 66.8% (p < 0.001)], Self-care [change by 61.0% (p < 0.001)], Usual activities [change by 97.1% (p < 0.001)], Pain/discomfort [change by 65.0% (p < 0.001)], and Anxiety/depression [change by 70.5% (p < 0.001)]. Significant reductions in EQ-5D-5L indices were also associated with greater inequalities in the distribution of health among age, gender, income, and educational groups. The EQ-5D-5L health gap among the poor was much greater (0.198), in comparison to richer (0.128) classes. Similar gaps were also found in terms of educational inequalities. The EQ-5D-5L health gap among those with primary education was 0.211, whereas for those with tertiary education it was 0.16. The Theil index indicated an increase in income-related HRQoL inequalities by 222.3% for the EQ-5D-5L index and by 124.2% for the EQ-VAS. The effects of demographic and socioeconomic variables on the EQ-VAS were found statistically significant: sex (p < 0.05), age (p < 0.001), education (p < 0.001), and income (p < 0.001). Conclusion The EQ-5D-5L instrument appears to be a powerful tool in assessing the health gap and the HRQoL inequalities among young people in Greece. The findings indicate the importance of developing effective health policies to combat inequalities and mitigate the impact of austerity measures on the quality of life of the young.